Orthodontic Treatment Acceleration: Exploring Methods and Future Frontiers - Ali abdullah alharbi,; Faisal Abdulrahman Saad Alkharisi,; Abdulmuhsen Saad Jafel,; Wejdan Ahmed Aljamaan,; Hatem Khaled Alahmary,; Aisha Matar Alshebani,; Ibrahim Abdullah Alrashed,; Fatimah Ahmed Al Nashery,; Latifah fadhel Alshameri,; Reem Matar Alshebani,; Naif Ahmed Alrumayyan, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The quest for accelerated orthodontic treatment has gained significant attention due to the potential benefits of reducing treatment duration, enhancing patient comfort, and minimizing adverse effects associated with prolonged treatment. This paper provides a comprehensive review of the past, present, and future perspectives on accelerated orthodontics (AO). Historically, surgical approaches, such as corticotomy and micro-osteoperforations, have aimed to exploit the regional acceleratory phenomenon (RAP) by inducing localized bone remodeling. Non-surgical approaches, including pharmacological agents (e.g., prostaglandins, relaxin, parathyroid hormone, vitamin D analogues) and physical modalities (e.g., low-level laser therapy, photobiomodulation, vibrational devices, magnetic fields), have also been explored. While these methods have demonstrated potential in accelerating tooth movement, the evidence regarding their efficacy and safety remains conflicting. Future perspectives include combination therapies, personalized approaches tailored to individual patient characteristics, and the integration of bioengineering and regenerative medicine techniques. Advancements in imaging and monitoring technologies may also contribute to optimizing treatment protocols and minimizing adverse effects. Ultimately, the pursuit of accelerated orthodontics should strike a balance between efficacy, safety, and patient acceptance, adhering to ethical principles and evidence-based practices.